1984
DOI: 10.1007/bf00293879
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic effects of small, distal Xq deletions

Abstract: The effects of small, distal Xq deletions (Xq26----qter) have been reviewed in light of three cases of our own and five from the literature. The symptoms caused by such deletions range from apparently none through irregular menstruation to secondary amenorrhea (or premature menopause) to primary amenorrhea. That the abnormal chromosome has any effects when it is inactivated may best be explained by one or by a combination of the following hypotheses. (1) the Xq-chromosome might exert an effect during developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…The mother was dead when the family was studied, but she was reported as normal except for early onset of menopause at 25 years of age. A third family was described by Trunca et al: 15 the patient had irregular menses for few years and amenorrhea at 18 years of age. One sister and the mother had the same deletion.…”
Section: Discussionmentioning
confidence: 98%
“…The mother was dead when the family was studied, but she was reported as normal except for early onset of menopause at 25 years of age. A third family was described by Trunca et al: 15 the patient had irregular menses for few years and amenorrhea at 18 years of age. One sister and the mother had the same deletion.…”
Section: Discussionmentioning
confidence: 98%
“…[15] Studies on the deletion of the Xq have revealed that in most of these cases the breaks occur within the critical Xq13q27 region. [16] The fact that a patient with an absence of long arm of X chromosome had normal stature suggests that the presence of short arm of X chromosome maintains the stature of the affected. Deletion involving the long arm of X chromosome generally results in ovarian failure if they involve the proposed critical region Xq13-q26.…”
Section: Discussionmentioning
confidence: 99%
“…Usually though, it is accompanied by dysmorphic features, which are not present in our case. Indeed, neither of these symptoms is expected in monosomy Xq27, as hemizygous males, and female heterozygotes for deletions involving this region are phenotypically normal (Trunca et al 1984). Thus, mental retardation in our case is probably related to the abnormal activity of the deleted X chromosome.…”
Section: Discussionmentioning
confidence: 74%